Synthesis in Trial Procedures? The Experience of the International Criminal Tribunals - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2001)
Critical to analysing the recent synthesis of criminal trialprocedures is an understanding of the internationalisation of criminal law andprocedure. As well as the creation of international tribunals to investigateand try crimes of world significance, there is emerging an internationaljurisprudence on criminal law (and procedural hybrids to support and developthis) which require integrated analysis.